Effect of arbuscular mycorrhizal fungi on physiological, bio-chemical and yield characters of wheat plants (Triticum aestivum L.) under drought stress conditions - Khaled Abdelaal; Abdulaziz Alaskar; Yaser Hafez (BMC Plant Biology)
Abstract This experiment was conducted to study the effect of inoculation with arbuscular mycorrhizal fungi (AMF) as an ecofriendly strategy on physiological, biochemical and yield characters of wheat plants. Our results showed a significant decrease in chlorophyll a and b as well as the maximum quantum efficiency of PSII (Fv/Fm) in wheat plants under drought conditions compared to control in the two seasons. Drought stress significantly reduced relative water content (RWC%) in the stressed plants compared with the control. Additionally, 1000 grain weight (g) and biological yield (t h− 1) were reduced significantly under drought stress. Furthermore, hydrogen peroxide (H2O2), Superoxide (O2 −), electrolyte leakage (EL%), lipid peroxidation (MDA) and total phenolic compounds were increased significantly in the stressed plants under drought conditions. However, wheat plants treated with AMF displayed a significant increase in chlorophyll concentrations and the maximum quantum efficiency of PSII as well as RWC% in the stressed wheat plants when compared with the stressed untreated plants. Our findings also indicated that application of AMF led to regulate the antioxidant enzymes activity, proline content and decrease hydrogen peroxide (H2O2), Superoxide (O2 −), electrolyte leakage (EL%) and lipid peroxidation (MDA) levels in the drought stressed wheat plants. Eventually, application of AMF as ecofriendly approach can improve wheat growth and grain yield of wheat plants by mitigating the adverse effects of drought stress. These results provide evidence for the important role of AMF in agricultural production and maximizing wheat grain yield.